2016
DOI: 10.5380/dma.v38i0.44352
|View full text |Cite
|
Sign up to set email alerts
|

Are National Parks Inherently Unequal? The 2006 French Park Reform and its Initial Implementation in Mainland France

Abstract: ABSTRACT:In France, like in other parts of the world, environmental-protection policies appear to have taken note of local resistance driven by the eviction of populations and restrictions on their use of certain areas. The amendment to the law on French national parks (2006 reform) as such recognized that local populations can help to protect natural environments, as well as their right to participate in defining the charter (or spatial plan) of new parks. This article analyses the creation and local acceptan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Overall, our study revealed that many local people perceive an unequal distribution of costs and benefits between, on the one hand, visitors and residents, and, on the other hand, among different sub-sets of the local community. This represents a social equity issue that may also need managing in order to maintain local public support the park, and which has been reported across many PA sites in both the global north and global south [61][62][63][64]. Negative impacts of overcrowding and disturbance were reported in qualitative data to particularly affect certain 'hotspot' areas, such as particular villages, concentrations of restaurants and access routes, and that benefits and costs within the park were very location-dependent.…”
Section: Social Equity Aspects In Eifel National Parkmentioning
confidence: 95%
“…Overall, our study revealed that many local people perceive an unequal distribution of costs and benefits between, on the one hand, visitors and residents, and, on the other hand, among different sub-sets of the local community. This represents a social equity issue that may also need managing in order to maintain local public support the park, and which has been reported across many PA sites in both the global north and global south [61][62][63][64]. Negative impacts of overcrowding and disturbance were reported in qualitative data to particularly affect certain 'hotspot' areas, such as particular villages, concentrations of restaurants and access routes, and that benefits and costs within the park were very location-dependent.…”
Section: Social Equity Aspects In Eifel National Parkmentioning
confidence: 95%